2011
DOI: 10.3171/2011.5.jns11185
|View full text |Cite
|
Sign up to set email alerts
|

Generation of chordoma cell line JHC7 and the identification of Brachyury as a novel molecular target

Abstract: Object Chordoma is a malignant bone neoplasm hypothesized to arise from notochordal remnants along the length of the neuraxis. Recent genomic investigation of chordomas has identified T (Brachyury) gene duplication as a major susceptibility mutation in familial chordomas. Brachyury plays a vital role during embryonic development of the notochord and has recently been shown to regulate epithelial-to-mesenchymal transition in epithelial-derived cancers. However, current understanding of the role of this transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
90
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 36 publications
(66 reference statements)
5
90
0
1
Order By: Relevance
“…Brachyury has been silenced in the JHC7 primary sacral chordoma cell line by shRNA in vitro, which arrested growth [42]. Nelson and associates searched for brachyury target genes with an integrated functional genomics approach, and brachyury was determined to activate transcription.…”
Section: Brachyurymentioning
confidence: 99%
“…Brachyury has been silenced in the JHC7 primary sacral chordoma cell line by shRNA in vitro, which arrested growth [42]. Nelson and associates searched for brachyury target genes with an integrated functional genomics approach, and brachyury was determined to activate transcription.…”
Section: Brachyurymentioning
confidence: 99%
“…11,12,14,20 To date, very few chordoma cell lines have been reported, namely U-CH1 17 and U-CH2b, 2 along with many more putative chordoma cell lines. Only a few of these have been shown to generate tumors in established mouse xenograft models and to retain molecular characteristics of the parent tumor and expanded cells.…”
mentioning
confidence: 99%
“…The CH1 and CH2 cells are no different in that respect. It can be hypothesized that if these cells were to regain brachyury expression, their proliferative capacity would increase since it has been shown that loss of brachyury in chordoma cultures induces growth arrest and senescence (21)(22)(23) Finally, assessing the difference in proliferation between cultured chordoma cells with enriched DMEM and enriched DMEM containing 33% FCM showed no apparent visual difference. However, in order to reliably conclude that the FCM supplementation does indeed have no effect, the proliferation pattern of both cultures needs to be assessed over longer time.…”
Section: Discussion / Conclusionmentioning
confidence: 99%